Aflatoxins from the endophytic fungus Aspergillus sp. Y-2 isolated from the critically endangered conifer Abies beshanzuensis. Issue 19 (2nd October 2021) - Zhu, Yuan-Xing; Peng, Cheng; Yu, Shui; Hu, Jin-Feng; Li, Jiyang
Abstract: Two new [asperxins A (1 ) and B (2 )] and four known (3 –6 ) aflatoxins were isolated and identified from the endophytic fungus Aspergillus sp. Y-2, which was derived from the needles of the critically endangered conifer Abies beshanzuensis . Their structures were elucidated by extensive spectroscopic methods. Among the isolates, compounds 1 and 5 showed considerable cytotoxicities against the A549 and Hela human cancer cell lines, with IC50 values in the range of 7.5–16.8 μM. Graphical Abstract: UF0001